2003
DOI: 10.1074/jbc.c300390200
|View full text |Cite
|
Sign up to set email alerts
|

The AP-2 Complex Is Excluded from the Dynamic Population of Plasma Membrane-associated Clathrin

Abstract: Numerous biologically relevant substrates are selectively internalized via clathrin-mediated endocytosis. At the plasma membrane the AP-2 complex plays a major role in clathrin coat formation, interacting with both cargo and clathrin. Utilizing simultaneous dual-channel total internal reflection fluorescence microscopy we have analyzed components of the AP-2 complex (␣-and ␤2-adaptin) during clathrin-mediated endocytosis. Although in static images enhanced green fluorescent protein-tagged AP-2 markers signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
86
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(112 citation statements)
references
References 35 publications
(30 reference statements)
21
86
5
Order By: Relevance
“…These events have been interpreted as CCV budding, movement, and uncoating. Because the GFP-␣ is not incorporated into the moving spots, it has been hypothesized that AP-2 is somehow swept aside as the vesicle buds (Rappoport et al, 2003(Rappoport et al, , 2005. Our results suggest an alternative interpretation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…These events have been interpreted as CCV budding, movement, and uncoating. Because the GFP-␣ is not incorporated into the moving spots, it has been hypothesized that AP-2 is somehow swept aside as the vesicle buds (Rappoport et al, 2003(Rappoport et al, , 2005. Our results suggest an alternative interpretation.…”
Section: Discussionmentioning
confidence: 60%
“…We initially inserted a GFP tag into our ␣ constructs as a way of localizing them, because GFP-tagged ␣ had been previously used for live cell imaging studies (Rappoport et al, 2003;Keyel et al, 2004;Rappoport et al, 2005). Some of the results of these studies have been puzzling, and our data may help to explain them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of dots was expressed as density of dots on the cell surface (dots/m 2 of surface). For the quantitation of EGFR/clathrin colocalization and the number of CCPs, HeLa cells were transfected with dsRed-clathrin (Rappoport et al, 2003) using lipofectAMINE reagent (Invitrogen, Carlsbad, CA), incubated for 16 h in SFM, placed on ice, and washed with prechilled SFM. Cells were then incubated with anti-EGFR (13A9 antibody) in SFM, in the presence or in the absence of EGF (100 ng/ml), 60 min at 0°C on a rocker, washed, fixed, and stained with an anti-mouse fluorochrome-labeled antibody.…”
mentioning
confidence: 99%
“…However, the role for AP-2 during the post-internalization phase has been controversial. Rappoport et al initially showed that AP-2 is lost from the CCV during internalization (Rappoport, Taha, Lemeer, et al, 2003), although Keyel et al later proposed that AP-2 accompanies CCVs into the cytosol, suggesting its possible regulatory role the downstream sorting machinery (Keyel, et al, 2004). However, more detailed TIRF image analysis confirmed the former hypothesis, and showed that while AP-2 was co-localized to static CCPs in the membrane, it was absent from those CCPs observed to disappear into the cytosol (Rappoport, et al, 2005).…”
Section: Understanding Clathrin Mediated Endocytosis Via Tirf Microscopymentioning
confidence: 99%